we have
(a+b)(3a-b)(2a+7b)
step 1
Solve
apply distributive property
(a+b)(3a-b)=3a^2-ab-3ab-b^2=3a^2-4ab-b^2
step 2
Multiply (3a^2-4ab-b^2) by (2a+7b)
6a^3+21a^2b-8a^2b-28ab^2-2ab^2-7b^3=6a^3+13a^2b-30ab^2-7b^3
answer is
<h2>6a^3+13a^2b-30ab^2-7b^3</h2>
Hello!
She placed 6 ribbons
2 at the ends and 5 every 3 meters
Answer:8 times 4+12+= 44
Step-by-step explanation:
8 times 4 gives you 32 then add 12 to get 44
Pick any two points
(0, 3), (-1,9)
Find slope (y2-y1)/(x2-x1)
(9-3)/(-1-0) = 6/-1 = -6
Y = -6x + b
Plug in a point
3 = 0 + b, b= 3
Final equation: y = -6x + 3
It is B my friend I worked it out non problem